Unexpected Acceleration in Treprostinil Delivery Administered by a Lenus Pro® Implantable Pump in Two Patients Treated for Pulmonary Arterial Hypertension - Kopp, Garance; Hachulla, Anne-Lise; Noble, Stéphane; Bringard, Aurélien; Soccal, Paola M.; Beghetti, Maurice; Lador, Frédéric (Frontiers in Medicine, 2020)
Keywords: pulmonary arterial hypertension; prostacyclin analogues; implantable pump; treprostinil delivery; internal device. Intravenous treprostinil administration by an implantable pump is an attractive option for pulmonary arterial hypertension (PAH) treatment and is the subject of recent publications. Short-term studies are promising, but there is still a lack of long-term prospective data. We analysed the treprostinil flow rate administered by the Lenus Pro® implantable pump in 2 patients suffering from PAH during follow-up times of respectively 4.2 and 3 years. The flow rate delivered by the pumps in these 2 patients exceeded the manufacturer admitted margin of error within 2 years and continued to increase to reach respectively 158% and 120% of the expected flow rate at the end of the follow up. In one case, the implantable pump had to be removed for this reason. The ex-vivo flow rate of the withdrawn pump determined in the laboratory reached 173% of the predicted value. This correlated with the in-vivo measurement, which suggests a continuous flow increase even after pump removal and without treprostinil use. Spontaneous flow increase from such an implantable pump is a potentially major pitfall, which needs to be identified and actively managed by the responsible clinicians.